(3GdMLGRjGJ ef TYQ GdTQja GdQVjs - (3CHhGdMSf eMeO Hf GdMSjf Hf ehSi GdQVhj GdYdhj GdMSjfj GdehShjs; (3GdTQja GdQVj , CHh GdMSf eMeO Hf GdMSjf Hf ehSi GdQVj GdYdhj GdMSjfj GdehShj, CHh GdMSf,J (B406 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdej, hGdUdGI hGdSdGe Ydi fHjg eMeO hBdg GdWGgQjf bGd GdTQja GdQVj aj GdZRd hGdfSjH(B: (3jGXHjI GdHGf JQYi aj NeGFdgG djgFc Gdjhe Ef GdbdH eQYGc s
(3BNQgG (B:s
(3jGYRd GdeTJGb OYg aEfg jWhj Ydi GdRaQGJ ZjQ MTGcG dh cGf bdHc bdHg eG deJg MGTGc eeG YfOg MGTGcG s
(3Vef eLehY , JQJjHgG (B: (3ef U (B286 - (3U(B305s
(3GdfSNI HgG MhGTs
(3fSNI KGdKIs
(3HgG TQhM hJYdjbGJ cKjQIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdCOHs